Kontribusi Self-Efficacy dan Job Demand terhadap Turnover Intention pada Karyawan Account Officer (AO) Usia Gen Z di PT X Padang - Hadikasuma, Nurul; Ayu, Rindang (Lembaga Yasin AlSys, 2025)
This study aims to analyze the contribution of self-efficacy and job demand to turnover intention among Generation Z Account Officers (AOs) at PT X Padang. The high resignation rate among Gen Z employees has become a strategic concern for the company, as it directly affects operational effectiveness and human resource costs. A quantitative approach with a correlational design was employed. The sample consisted of 120 AOs aged 18–29 years, selected using purposive sampling. The instruments used included the Self-Efficacy Scale (Schwarzer & Jerusalem, 1995), the Job Demand Scale (Bakker & Demerouti, 2014), and the Turnover Intention Scale (Mobley, 1978). Data were analyzed using multiple regression with SPSS version 25. The findings indicate that neither self-efficacy nor job demand—individually or jointly—have a significant effect on turnover intention. The coefficient of determination (R²) was 0.8%, suggesting that these two variables account for only a minimal proportion of the variance in employees’ intention to leave. These results suggest that turnover intention is more strongly influenced by other external factors, such as job satisfaction, career prospects, leadership style, and organizational support. The implications of this study emphasize the need for a holistic managerial approach focused on enhancing the work environment and improving both intrinsic and extrinsic factors to reduce turnover among Gen Z employees.